The Deadliest Diseases then and Now - Hopkinson, Deborah (New York : Scholastic Focus, 2021)
"The deadly outbreak of plague known as the Great Mortality, which struck Europe in the mid 1300s and raged for four centuries, wiped out more than 25 million people in the course of just two years. With its vicious onslaught, life changed for millions of people almost instantaneously. Deadly pandemics have always been a part of life, from the Great Mortality of the Middle Ages, to the Spanish Influenza outbreak of 1918, to the eruption of COVID-19 in our own century. Many of these diseases might have seemed like things to read about in history books -- until the unthinkable happened, and our own lives were turned upside down by the emergence of the novel coronavirus. As we learn more about COVID-19, we may be curious about pandemics of the past. Knowing how humans fought diseases long ago may help us face those of today. In this fast-paced, wide-ranging story filled with facts, pictures, and diagrams about diseases -- from plague to smallpox to polio to flu -- critically acclaimed Sibert Honor author Deborah Hopkinson brings voices from the past to life in this exploration of the deadliest diseases of then and now"--
Part One: The great mortality -- Part Two: PLague, plague, and more plague -- Part Three: Global disaster: The 1918 influenza pandemic -- Part Four: Other deadly diseases then and now -- Part Five: NOW: The twenty-first century.
Includes bibliographical references and index.
Keywords: Epidemics -- Juvenile literature. -- History; Influenza Epidemic, 1918-1919 -- Juvenile literature; Black Death -- Juvenile literature; COVID-19 (Disease) -- Juvenile literature; Epidemics -- History; Influenza Epidemic, 1918-1919; Black Death; COVID-19 (Disease)